Negotiating Patriarchal Relationship: Representation of Subjectification in Doja Cat’s Woman (2021) Music Video - Afriano, Reno; Hapsari, Nurul Fitri; Puspita, Yulia Mega; Tiantini, Wendy Belinda (Universitas Sanata Dharma, 2024)
This study aims to illustrate the subjectification of women's bodies as one of the notions of postfeminist sensibility. Subjectification involves depicting women in a patriarchal setting as empowered individuals with agency, highlighting their reservoirs of strength and spheres of influence, challenging the perception of complete powerlessness. The object of investigation in this study is the music video by Doja Cat entitled